1989
DOI: 10.1093/cvr/23.8.723
|View full text |Cite
|
Sign up to set email alerts
|

Collagen accumulation in heart ventricles as a function of growth and aging

Abstract: Increase in resting tension of left ventricular papillary muscle with age has been attributed to the amount of collagen present. We therefore studied the total amount and structure of myocardial collagen as a function of age in the hearts of male Fischer 344 rats. Using amino acid analysis and quantification of hydroxyproline, we showed that collagen accumulates in relation to ventricular protein after 3 months of age and continues in that mode with increased age of the animal, levelling off at 22 months. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 0 publications
9
66
0
3
Order By: Relevance
“…Our results are also consistent with investigations showing that cardioprotective treatments are mediated by a restoration or up-regulation of antioxidant enzymes (42,45). It is recognized that an increase in collagen concentration is an integral part of the extracellular matrix remodeling that takes place in the LVs during the natural aging process (66) and as well as in response to a variety of pathologies resulting in hypertrophy of this chamber (67,68). In accordance with these studies, we showed evidence of an increase of collagen deposition with aging and its exacerbation in aged SHR.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also consistent with investigations showing that cardioprotective treatments are mediated by a restoration or up-regulation of antioxidant enzymes (42,45). It is recognized that an increase in collagen concentration is an integral part of the extracellular matrix remodeling that takes place in the LVs during the natural aging process (66) and as well as in response to a variety of pathologies resulting in hypertrophy of this chamber (67,68). In accordance with these studies, we showed evidence of an increase of collagen deposition with aging and its exacerbation in aged SHR.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier pathological studies in human and in rat have reported increased myocardial fibrosis in aged hearts (Tomanek et al 1972;Eghbali et al 1989;Besse et al 1993). Similarly our results showed that the total protein levels were maintained in the senescent group while the collagen levels were increased.…”
Section: Discussionsupporting
confidence: 88%
“…These areas of interstitial fibrosis, predominantly in the subendocardium of the left ventricle, increase with age and may be related to the loss of myocyte volume as "replacement fibrosis." 22,24 Connective tissue content and collagen cross-linking also decreased with endurance training. 25,26 Furthermore, exercise appears to have an antiapoptotic effect on myocytes that likely enhances chamber distensibility because myocytes are less stiff than collagen.…”
Section: Physiologic Differences Between Ventricular Compliance and Rmentioning
confidence: 97%